+
= ![\frac{2c}{x-c} \frac{2c}{x-c}](https://tex.z-dn.net/?f=%5Cfrac%7B2c%7D%7Bx-c%7D)
Solve for x
Answers
Answered by
0
Given,a/(x-a) + b/(x-b) = 2c/(x-c)
[a(x-b)+b(x-a)]/(x-a)(x-b) = 2c/(x-c)
(x-c)[a(x-b)+b(x-a)] = 2c(x-a)(x-b)
ax2 – 2abx + bx2 - acx + 2abc – bcx = 2cx2 – 2bcx – 2acx + 2abc
ax2+ bx2 - 2cx2 = 2abx – acx – bcx
(a+b-2c)x2 = x(2ab – ac – bc)
(a+b-2c)x2 - x(2ab – ac – bc) = 0
x[(a+b-2c)x - (2ab – ac – bc)] = 0
x = 0 or (a+b-2c)x - (2ab – ac – bc) =0
x = 0 or (a+b-2c)x = (2ab – ac – bc)
x = 0 or x = (2ab – ac – bc) / (a+b-2c)
thus the 2 roots of the given equation are x = 0 and x = (2ab – ac – bc) / (a+b-2c)
hope it's helps
please mark me as brainliest
Similar questions
Business Studies,
8 months ago
Geography,
8 months ago
Math,
8 months ago
Biology,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago